2022
DOI: 10.21203/rs.3.rs-1984365/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Protective and risk factors of recurrent severe hypoglycemia in adults with type 1 diabetes: A cross-sectional analysis of baseline data from the PR-IAH study

Abstract: Background Severe hypoglycemia (SH) remains a central problem in the management of type 1 diabetes (T1D); however, little is known about the protective and risk factors associated with recurrent SH (RSH). This study aimed to identify the protective and risk factors for RSH in adults with T1D. Methods This cross-sectional study enrolled 287 adults with T1D (mean age: 50.3 ± 14.5 years, male: 36.2%, diabetes duration: 17.6 ± 11.2 years, mean HbA1c: 7.7 ± 0.9%) and divided them into non-SH (n = 262), solitary S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 49 publications
0
1
0
Order By: Relevance
“…(2022) verified this finding (35) who disclosed that renal problems affected 25% of the participants under study. Also, this finding was agreed with Sankar and Jayakrishnan (2023) (36) who found that most of sample of the studied patients had liver diseases.…”
Section: Discussionmentioning
confidence: 70%
“…(2022) verified this finding (35) who disclosed that renal problems affected 25% of the participants under study. Also, this finding was agreed with Sankar and Jayakrishnan (2023) (36) who found that most of sample of the studied patients had liver diseases.…”
Section: Discussionmentioning
confidence: 70%